2023
DOI: 10.1021/acsami.3c05337
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Enzyme Cascade-Triggered Nitric Oxide Release Nanoplatform Combined with Chemo Starvation-like Therapy for Multidrug-Resistant Cancers

Ge Li,
Xinyue Lu,
Shixin Zhang
et al.

Abstract: Tumor drug resistance has long been a major challenge in medical oncology. Ferroptosis is a form of regulated cell death with promising clinical applications. However, the efficacy of ferroptosis-inducing agents is often limited by endogenous factors when used alone, and thus, synergistic therapy offers a promising strategy to address this issue. In this study, we developed an iron-doped metal–organic framework (MOF), Fe/ZIF-8, loaded with glucose oxidase (Gox), l-arginine (l-arg), and adriamycin hydrochloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…They found that H 2 O 2 from GOx catalysis and ˙OH from iron-mediated Fenton reactions could catalyse l -arg to release nitric oxide (NO), which subsequently inhibited the P -glycoprotein expression and enhanced intracellular DOX levels, amplifying the chemotherapeutic effect. 123 Despite the effectiveness, the above encapsulating strategies may encounter uncontrolled drug leakage, resulting in side effects to normal tissues. In this regard, the prodrug concept has been introduced.…”
Section: Metabolism-targeted Nanomedicine For Cancer Therapymentioning
confidence: 99%
“…They found that H 2 O 2 from GOx catalysis and ˙OH from iron-mediated Fenton reactions could catalyse l -arg to release nitric oxide (NO), which subsequently inhibited the P -glycoprotein expression and enhanced intracellular DOX levels, amplifying the chemotherapeutic effect. 123 Despite the effectiveness, the above encapsulating strategies may encounter uncontrolled drug leakage, resulting in side effects to normal tissues. In this regard, the prodrug concept has been introduced.…”
Section: Metabolism-targeted Nanomedicine For Cancer Therapymentioning
confidence: 99%
“…Therefore, efficient delivery of l -Arg intratumoral to achieve responsive NO release is essential for improving antimetastatic efficacy. Inspired by the cascade response of Gox-mediated starvation therapy and l -Arg-mediated NO therapy, some efforts have been made for the intratumoral delivery of Gox and l -Arg. , However, most nanocarriers possess a lower Gox-loading efficiency and poor stability. In addition, scant attention has been focused on tumor metastasis, especially hypoxia-induced metastasis arising from Gox-mediated starvation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on NO have shown great promise in anti-inflammatory as well as anticancer properties, which are essentially concentration dependent . At a very low concentration (pM-nM), it helps in vasodilation to augment cancer cell infiltration, whereas at an elevated concentration (μM-mM), it turns out to be a killer one by oxidation and nitrosative stress. , Therefore, the presence of the required amount of NO in the tumor microenvironment (TME) inhibits the expression of mammalian HIF-1α, base-excision DNA repair enzyme, and NF-kB activation and the overexpression of a transmembrane P-glycoprotein (P-gp) which is involved in ATP-dependent drug effluxing from cancer cells. , Moreover, NO is also very much reactive with superoxide (O 2 .– ) to generate more highly reactive ONOO – to induce the oxidation of DNA and proteins and further sensitizing radiotherapy, phototherapy, and chemodynamic therapy. , Due to the significant role of NO in inhibiting the tumor growth and subsequent progression, there is ever increasing curiosity in maneuvering the therapeutic potential of NO to overcome the multidrug resistance (MDR) for cancer cell killing. As NO is a free radical with very limited stability, a prolific design of NO-releasing donor moieties with proper release characteristics at the desired concentration range is a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 Therefore, the presence of the required amount of NO in the tumor microenvironment (TME) inhibits the expression of mammalian HIF-1α, base-excision DNA repair enzyme, and NF-kB activation and the overexpression of a transmembrane P-glycoprotein (P-gp) which is involved in ATP-dependent drug effluxing from cancer cells. 26 , 27 Moreover, NO is also very much reactive with superoxide (O 2 .– ) to generate more highly reactive ONOO – to induce the oxidation of DNA and proteins and further sensitizing radiotherapy, phototherapy, and chemodynamic therapy. 28 , 29 Due to the significant role of NO in inhibiting the tumor growth and subsequent progression, there is ever increasing curiosity in maneuvering the therapeutic potential of NO to overcome the multidrug resistance (MDR) for cancer cell killing.…”
Section: Introductionmentioning
confidence: 99%